Investor sentiment and stock return volatility: Evidence from the Johannesburg Stock Exchange - Lorraine Rupande; Hilary Tinotenda Muguto; Paul-Francois Muzindutsi (Cogent Economics & Finance, 2019)
Volatility is an important component of asset pricing; an increase in volatility on markets can trigger changes in the risk distribution of financial assets. In conventional financial theory, investors are considered to be rational and any changes in relevant risk are assumed to be a result of the movement in fundamental factors. However, herein this study, it is hypothesized that there are movements in risk that are driven by volatility linked to sentiment-driven noise trader activity whose patterns are irreconcilable with changes in fundamental factors. This assertion is tested using a daily sentiment composite index constructed from a set of proxies and Generalised Autoregressive Conditional Heteroscedasticity models on the South African market over a period spanning July 2002 to June 2018. The results show that there is a significant connection between investor sentiment and stock return volatility which shows that behavioural finance can significantly explain the behaviour of stock returns on the Johannesburg Stock Exchange. It is, thus, recommended that due to the inadequacies of popular asset pricing models such as the Capital Asset Pricing Model, consideration should be made towards augmenting these asset pricing models with a sentiment risk factor.
Keywords: G11; G12; G14; G40; G41; 330; Generalised autoregressive conditional heteroscedasticity model (GARCH); investor sentiment; stock return volatility; noise traders